NIGHT AT THE LIBRARY SEBAGAI STRATEGI MARKETING DI PERPUSTAKAAN CIKINI - Ananda Putri Febrina; Ika Krismayani (Pustakaloka, 2026)
Libraries face challenges in attracting visitors, particularly young people, due to the dominance of digital media and the perception that libraries are less attractive public spaces. More creative experiential marketing strategies are needed to maintain libraries' relevance. This study analyzes Night at the Library (NATL), a program developed by the Cikini Library, as a library marketing strategy using the 7P services marketing mix framework and examines its contribution to strengthening the library's image and attractiveness. A qualitative case study approach was employed. Data were collected through semi-structured interviews, non-participant observation, and document analysis involving four purposively selected participants. The data were analyzed thematically using the 7P framework and validated through source triangulation. The findings indicate that NATL enhances the library's image, expands its marketing reach, enriches visitor experiences through diverse literacy and arts activities, and demonstrates adaptability in responding to challenges and opportunities in library management. The creative management of the product, process, people, and physical evidence elements illustrates the application of the 7P services marketing mix in library services. This study provides theoretical contributions to library marketing research and practical contributions to public libraries by offering insights for developing experiential marketing strategies. The findings also suggest that the involvement of volunteers and interns can support program sustainability and serve as a replicable model for other libraries seeking to enhance service innovation and visitor engagement.